A comparison of use Diode LASER with conventional surgery for the management of turbinates hypertrophy - علي, ياسر; يوسف , يوسف; شريبا , مجد (Latakia University Journal -Medical Sciences Series, 2022)
Background: Nasal obstruction and difficulty of nasal breathing resulting from the hypertrophy of nasal turbinates is one of the most important symptoms in ENT. There are many (conventional) surgical procedures used in the management of the hypertrophy of nasal turbinates, but most of these procedures are associated with a risk of bleeding, pain and damage to the mucous membrane, so we need a safer method. Diode LASER is a new technology in the management of the hypertrophy of nasal turbinates. Objectives: Comparison between the use of Diode LASER and conventional surgical methods in the management of the hypertrophy of nasal turbinates and evaluation of the features and benefits offered by Diode LASER. Methods: The study was a comparative prospective study conducted at the department of ENT، Tishreen University Hospital، lattakia، Syria done between January 2020 to October 2021. 60 patients (33 male and 27 females) were enrolled in the study and divided into two groups depending on the used surgical method. Group1 : conventional surgical method، Group2 : Diode LASER surgery. Then comparing the results during and after 2days, 2weeks,1month, 3months, 6months of the surgery. Results: There were a significant difference between study groups in the mean time required for surgery (shorter in group2 with p-value <0.01) and blood loss, pain ,require nasal packs (less in group2 with p-value<0.01). The improvement of symptoms after surgery is higher when using Diode LASER (p-value <0.05) , the recurrence was higher after 6 months with conventional surgical methods (p-value <0.01). Conclusion: Using Diode LASER in the surgical management of of the hypertrophy of nasal turbinates is an effective and safe method because it saves time during surgery, reduces bleeding, pain, and the need for nasal packs, and the improvement of symptoms is higher and the recurrence is lesser, compared to conventional surgical methods.